Understanding Appearance-Enhancing Drug Use in Sport Using an Enactive Approach to Body Image - Hauw, Denis; Bilard, Jean (Frontiers in Psychology, 2017)
From an enactive approach to human activity, we suggest that the use of appearance-enhancing drugs is better explained by the sense-making related to body image rather than the cognitive evaluation of social norms about appearance and consequent psychopathology-oriented approach. After reviewing the main psychological disorders thought to link body image issues to the use of appearance-enhancing substances, we sketch a flexible, dynamic and embedded account of body image defined as the individual’s propensity to act and experience in specific situations. We show how this enacted body image is a complex process of sense-making that people engage in when they are trying to adapt to specific situations. These adaptations of the enacted body image require effort, perseverance and time, and therefore any substance that accelerates this process appears to be an easy and attractive solution. In this enactive account of body image, we underline that the link between the enacted body image and substance use is also anchored in the history of the body’s previous interactions with the world. This emerges during periods of upheaval and hardship, especially in a context where athletes experience weak participatory sense-making in a sport community. We conclude by suggesting prevention and intervention designs that would promote a safe instrumental use of the body in sports and psychological helping procedures for athletes experiencing difficulties with substances use and body image.